MGNREGA, power politics, and computerization in Andhra Pradesh - Masiero, Silvia; Maiorano, Diego (Taylor & Francis, 2017)
The link between e-governance and accountability of state administrations for service provision has been problematized in the literature to date. However, little is known about its application to anti-poverty programmes, of which public workfare schemes are an increasingly important subset. In this paper we fill the gap with a study of MGNREGA, India’s largest workfare scheme, as it is being computerized in the southern state of Andhra Pradesh. A state-level information system was devised to ensure transparency of transactions, and hence combat the illicit diversion of the programme’s funds to non-entitled recipients. But while doing so, the system carries a policy of centralization, which concentrates decision-making power in the hands of a limited set of actors rather than distributing it across the programme’s stakeholders. In particular the Field Assistants, appointed officials responsible for the village-level management of the scheme, have direct control on the information inputted in the system, which reinforces their position of authority rather than challenging it in favor of greater empowerment of wageseekers. Furthermore, wage payments are traced by the information system till they reach the disbursement agencies, but are prone to capture in the “last mile” where workers collect their salaries, which results in greater vulnerability for them. As a result, MGNREGA workers are constructed by the new information system as sheer beneficiaries rather than active participants in the programme, which concurs to crystallizing power structures rather than resulting in wageseekers’ empowerment. Lessons are drawn for other states currently computerizing their social safety nets.